Postnatal gestational age estimation using newborn screening blood spots: a proposed validation protocol. Issue 2 (27th July 2017) - Murphy, Malia S Q; Hawken, Steven; Atkinson, Katherine M; Milburn, Jennifer; Pervin, Jesmin; Gravett, Courtney; Stringer, Jeffrey S A; Rahman, Anisur; Lackritz, Eve; Chakraborty, Pranesh; Wilson, Kumanan
Abstract : Background: Knowledge of gestational age (GA) is critical for guiding neonatal care and quantifying regional burdens of preterm birth. In settings where access to ultrasound dating is limited, postnatal estimates are frequently used despite the issues of accuracy associated with postnatal approaches. Newborn metabolic profiles are known to vary by severity of preterm birth. Recent work by our group and others has highlighted the accuracy of postnatal GA estimation algorithms derived from routinely collected newborn screening profiles. This protocol outlines the validation of a GA model originally developed in a North American cohort among international newborn cohorts. Methods: Our primary objective is to use blood spot samples collected from infants born in Zambia and Bangladesh to evaluate our algorithm's capacity to correctly classify GA within 1, 2, 3 and 4 weeks. Secondary objectives are to 1) determine the algorithm's accuracy in small-for-gestational-age and large-for-gestational-age infants, 2) determine its ability to correctly discriminate GA of newborns across dichotomous thresholds of preterm birth (≤34 weeks, <37 weeks GA) and 3) compare the relative performance of algorithms derived from newborn screening panels including all available analytes and those restricted to analyte subsets. The study population will consist of infants born to mothers already enrolled in one of two preterm birth cohorts in Lusaka, Zambia, and Matlab, Bangladesh. Dried blood spot samples will be collected and sent for analysis in Ontario, Canada, for model validation. Discussion: This study will determine the validity of a GA estimation algorithm across ethnically diverse infant populations and assess population specific variations in newborn metabolic profiles.